Recolonization by ants in bauxite mines rehabilitated by a number of different methods - Majer, Jonathan; Day, J. E.; Kabay, E.; Perriman, W. (1984)
(1) The ant fauna of thirty bauxite mines rehabilitated by a range of different methods and three forest controls was surveyed in the summer of 1978-70. Physical and botanical parameters were also measured.(2) Forty-two species of ants were found in the rehabilitated areas although many of the original forest species were not yet present.(3) Eight ant community parameters were initially screened by canonical analysis. Ant species diversity (H') and ant species richness were found to be the most useful measures for relating to mined area parameters.(4) Multiple regression analysis using ant species richness and species diversity as dependent variables revealed that ant return was positively associated with plant species richness and diversity, time since rehabilitation, percentage plant cover and percentage litter cover. Presence of large logs was also an important factor.(6) Principal components ordination analysis of the data suggest that plant species richness, and diversity, rehabilitation age and percentage litter cover also influence the species composition of the ant community in rehabilitated areas.(6) The relevance of the findings to the improvement of rehabilitation practices is discussed.